2000
DOI: 10.1046/j.1365-2052.2000.00622.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic and breed distribution of an Msp I PCR‐RFLP in the bovine growth hormone (bGH) gene

Abstract: Information is presented on the frequency of the Msp I (-) allele in the third intron of the bovine growth hormone gene in a large number of cattle breeds. Consideration of the breed frequencies in relation to their geographic origin shows a low frequency for breeds originating in Northern Europe, moderate frequencies for breeds originating in Eastern Europe or the countries surrounding the Mediterranean basin, and very high frequencies for breeds originating in the Indian subcontinent. Consideration of breed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
20
0
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 9 publications
7
20
0
4
Order By: Relevance
“…Most Zebu breeds have a α S1 -cas C gene frequency of about 0.9, whereas it is very unusual for European breeds to have a gene frequency above 0.5 for this variants, and it is usually around 0.1 or less in the North-European and Pied Lowland breeds. Besides, in Bos taurus, the GH locus was found to have two alleles, whereas it was monomorphic (allele L only) in Zebu breeds (Lagziel et al, 2000;Arranz Santos, 1994;Kemenes et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most Zebu breeds have a α S1 -cas C gene frequency of about 0.9, whereas it is very unusual for European breeds to have a gene frequency above 0.5 for this variants, and it is usually around 0.1 or less in the North-European and Pied Lowland breeds. Besides, in Bos taurus, the GH locus was found to have two alleles, whereas it was monomorphic (allele L only) in Zebu breeds (Lagziel et al, 2000;Arranz Santos, 1994;Kemenes et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…At locus GH, the breed frequencies of allele GH A, as related to their geographical origin, show a low frequency for breeds stemming from Northern Europe, moderate frequencies for breeds from Eastern Europe or the countries surrounding the Mediterranean basin, and very high frequencies for breeds from the Indian subcontinent (Lagziel et al, 2000). The GH A range of gene frequencies found in Argentine and Bolivian Creole (0.757-1.00), Iberian (0.396-0.955), and other South-American Creole cattle breeds were overlapping (Arranz Santos, 1994;Arranz Santos et al, 1996;Kemenes et al, 1999;Reis et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the MspI ( -) allele frequencies in zebu cattle are different (relatively high frequencies) from those reported for taurine breeds (Bos taurus) from northern Europe, Mediterranean countries, and North America. For instance, 0.000 and 0.026 were reported in the Holstein breed (Zhang et al, 1993a;Lagziel et al, 2000;Zhou et al, 2005), 0.000 in Hereford and in N'Dama, 0.150 in Jersey, 0.140 in Angus, 0.190 in Red Danish (Lagziel et al, 2000), and 0.050 in Norwegian Red and in Red Danish (Høj et al, 1993). Table 4 suggests that the frequency range of the MspI ( -) allele is 0.100 and 0.390 for cattle breeds of northern Europe, the United States, Europe, and the Mediterranean (Lagziel et al, 2000;Öner et al, 2011), but 0.670 to 0.940 in indicine (zebu) cattle breeds (Sodhi et al, 2007).…”
Section: Gh-mspi and Gh-alui Polymorphismsmentioning
confidence: 99%
“…Various investigations revealed associations between GH-MspI polymorphism and both famele and male reproductive traits [48][49][50] . At the same time, it was observed that the distribution of this polymorphism obviously differed between geographic regions [51,52] . The A allele was predominant among breeds from Europe while the frequency of B allele was higher among Bos indicus cattle [51,52] .…”
Section: As It Is Seen Inmentioning
confidence: 84%
“…At the same time, it was observed that the distribution of this polymorphism obviously differed between geographic regions [51,52] . The A allele was predominant among breeds from Europe while the frequency of B allele was higher among Bos indicus cattle [51,52] . The B allele was found related to meat quality and the lower frequencies of the allele among HolsteinFrisian cows were explained with this finding [23] .…”
Section: As It Is Seen Inmentioning
confidence: 84%